Tinjauan Yuridis Terhadap Wanprestasi dalam Perjanjian Jual Beli Tanah Warisan (Studi Putusan Pengadilan Negeri Medan Nomor: 376/Pdt.G/2017/PN.Mdn) - Reza Aulia HP; Taufik Siregar; Dessy Agustina Harahap (JUNCTO: Jurnal Ilmiah Hukum, 2021)
Buying and selling can be said to be valid if all the conditions are met. The inheritance sale law is the same as the general sale law, but if the inheritance object is the right to the land to be sold, all heirs must participate in the sale of the inheritance. One example of a dispute that occurred in the sale and purchase of inheritance land during the transaction process of buying and selling inherited land, the buyer has paid / submitted an amount of money in accordance with the agreement on the price of land to the seller, but the seller did not immediately submit a letter of approval of sale from all heirs it sells to buyers as in decision number 376 / Pdt.G / 2017 / Pn.Mdn. Legal arrangements regarding buying and selling are regulated in Article 1457 of the Civil Code in selling and selling inheritance assets in general the same as buying and selling in general, but if the object of buying and selling is inheritance, all heirs must make an heir certificate. With the Default, the legal consequences that arise are the agreements made by the parties can be canceled or canceled by themselves. However, if one party feels aggrieved due to the failure to carry out the achievement of the agreement, then one of the parties has a right to sue in an effort to enforce the rights of the contract or agreement.